Optimization using Adjusted Program Budget Marginal-Analysis (PBMA) for Decision Making Process and Budget Planning Purposes - Bilkisu Maijamaa (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2021)
Program budget marginal-analysis is a framework used by decision makers to allocate and reallocate resources with maximized benefit or specified goals. Evidently most application of PBMA as employed in most studies have focused mainly within the health organization. To implement the PBMA for optimizing budget allocation problems it involves seven stages. This research will look at applying the PBMA in other organizations that are strategically based for budget allocations. To implement on other organizations, some adjustment on the existing PBMA need to be made. This was achieved through introduction of suitable quantitative approach instead of using the traditional qualitative approach to calculate the marginal cost for the activities/strategies. By introducing and implementation of a suitable mathematical programming model for the final budget allocation process. The adjusted PBMA has proven to be a flexible and workable framework that can be used in other organization not just the health sector where it originated. Hence it is recommended to be used by other organizations for optimal budget allocations